Eye-Tracking Reveals that the Strength of the Vertical-Horizontal Illusion Increases as the Retinal Image Becomes More Stable with Fixation - Chouinard, Philippe A.; Peel, Hayden J.; Landry, Oriane (Frontiers in Human Neuroscience, 2017)
The closer a line extends toward a surrounding frame, the longer it appears. This is known as a framing effect. Over 70 years ago, Teodor Kunnapas demonstrated that the shape of the visual field itself can act as a frame to influence the perceived length of lines in the vertical-horizontal illusion. This illusion is typically created by having a vertical line rise from the center of a horizontal line of the same length creating an inverted T figure. We aimed to determine if the degree to which one fixates on a spatial location where the two lines bisect could influence the strength of the illusion, assuming that the framing effect would be stronger when the retinal image is more stable. We performed two experiments: the visual-field and vertical-horizontal illusion experiments. The visual-field experiment demonstrated that the participants could discriminate a target more easily when it was presented along the horizontal versus vertical meridian, confirming a framing influence on visual perception. The vertical-horizontal illusion experiment determined the effects of orientation, size, and eye gaze on the strength of the illusion. As predicted, the illusion was strongest when the stimulus was presented in either its standard inverted T orientation or when it is rotated 180° compared to other orientations, and in conditions in which the retinal image was more stable, as indexed by eye tracking. Taken together, we conclude that the results provide support for Teodor Kunnapas’ explanation of the vertical-horizontal illusion.